Genetic Predictors of Cognitive Decline and Labor Market Exit - Anne Katrine Borgbjerg; Esben Agerbo; Nabanita Datta Gupta; Timothy J. Halliday (Institute of Labor Economics (IZA), 2025)
We analyze administrative and genetic data from over 200,000 Danes to study the effects of genetic risk for Alzheimer's Disease (AD) on labor market outcomes. Higher AD genetic risk increases dementia diagnoses and GP visits for both genders. Among women aged 45–65, it reduces labor participation and raises disability pension uptake, especially near retirement. These effects weaken for women with high polygenic scores for education. For men, AD genetic risk shows no employment impact. These gender differences align with evidence that AD genetic markers are more predictive in women.
Keywords: I14; J14; J22; 330; Alzheimer's Disease; labor supply; genoeconomics